2018
DOI: 10.1111/cbdd.13434
|View full text |Cite
|
Sign up to set email alerts
|

One pot multi‐component synthesis of functionalized spiropyridine and pyrido[2,3‐d]pyrimidine scaffolds and their potent in‐vitro anti‐inflammatory and anti‐oxidant investigations

Abstract: A new series of functionalized fused pyridines 4(a–i) and fused pyrido[2,3‐d]pyrimidines 8(a–c) were designed and synthesized through a multi‐component reaction where in pyridine ring formation step plays a key role. All the newly formed compounds were well characterized by spectral techniques such as FTIR, 1HNMR, 13CNMR, HRMS and XRD. The potential therapeutic activities such as anti‐inflammatory activity by protein denaturation and RBC membrane stabilization methods, and anti‐oxidant activity by DPPH scaveng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Lavanya et al reported two different pyridine scaffolds 474-475 via one pot MCR (Scheme 88, 89). [108] When the reaction was carried out using pyrrolidine, malononitrile and cyclic ketone 351 in ethanol at room temperature spiropyridine derivatives 474 were formed 474 and pyrido[2, 3-d] pyrimidine derivatives 475 a number of the synthesized compounds have display have higher antioxidant activity compared to ascorbic acid and equivalent antiinflammatory efficacy to the conventional drug diclofenac. In 2020, our groups developed a simple, efficient and chemoselective synthetic route for the synthesis of pyridine fused spirooxindole derivatives 484 via Brønsted acid catalyzed three component tandem Knoevenagel/Michael addition reaction (Scheme 90).…”
Section: Synthesis Of Pyridines and Quinolinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lavanya et al reported two different pyridine scaffolds 474-475 via one pot MCR (Scheme 88, 89). [108] When the reaction was carried out using pyrrolidine, malononitrile and cyclic ketone 351 in ethanol at room temperature spiropyridine derivatives 474 were formed 474 and pyrido[2, 3-d] pyrimidine derivatives 475 a number of the synthesized compounds have display have higher antioxidant activity compared to ascorbic acid and equivalent antiinflammatory efficacy to the conventional drug diclofenac. In 2020, our groups developed a simple, efficient and chemoselective synthetic route for the synthesis of pyridine fused spirooxindole derivatives 484 via Brønsted acid catalyzed three component tandem Knoevenagel/Michael addition reaction (Scheme 90).…”
Section: Synthesis Of Pyridines and Quinolinesmentioning
confidence: 99%
“…Lavanya et al. reported two different pyridine scaffolds 474–475 via one pot MCR (Scheme 88, 89) [108] . When the reaction was carried out using pyrrolidine, malononitrile and cyclic ketone 351 in ethanol at room temperature spiropyridine derivatives 474 were formed with 61–88 % yield.…”
Section: Six‐membered Heterocyclic Compoundsmentioning
confidence: 99%
“…In vitro studies revealed that the compounds exhibited equivalent anti-inflammatory activity with reference to diclofenac. While the most active derivatives 59a and 59b showed excellent anti-oxidant activity and anti-inflammatory activity (Lavanya et al, 2019).Wang et al evaluated the hybrid of pyrido[2,3-d]pyrimidine-2,4-dione with benzoxazinone for herbicidal activity through protoporphyrinogen oxidase inhibition. All the synthesized compounds were exhibited promising herbicidal activity.…”
Section: Miscellaneous Activitymentioning
confidence: 99%
“…Furthermore, pyridine derivatives of different heterocyclic compounds have shown an important pharmacological properties like antifungal, antitubercular, antibacterial, antimicrobial, insecticidal. [10,11] It was reported that heterocyclic pyridine derivatives have a broad range of significant biological activities such as antimicrobial, [12][13][14][15] antiviral, [16][17][18] antioxidant, [19][20][21] cytotoxic with anticancer, and antitumor activities. [22][23][24][25][26][27][28] The desire for pyridine and its derivatives has further increased over the last 50 years by the discovery of many bioactive compounds containing pyridine by several companies.…”
Section: Introductionmentioning
confidence: 99%